2010
DOI: 10.1007/s00198-010-1255-9
|View full text |Cite
|
Sign up to set email alerts
|

Change in hip fracture incidence over the last 6 years in France

Abstract: Over the last 6 years, the incidence of hip fractures decreased in women aged over 39 years and increased in men aged over 39 years; a decrease in the incidence of these fractures was observed in both genders in the elderly. Such epidemiological data may help policy making, planning resource allocation, and setting up complementary health decisions for the management of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 17 publications
5
24
1
2
Order By: Relevance
“…We found that the incidence of hip fractures decreased in women as previously reported (19) and a small variation of the incidence per million from 1369 to 1476 in men. A fall in the incidence of hip fractures had already been reported previously for a period of 11 years in women, (16,18) but not consistently in men.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the incidence of hip fractures decreased in women as previously reported (19) and a small variation of the incidence per million from 1369 to 1476 in men. A fall in the incidence of hip fractures had already been reported previously for a period of 11 years in women, (16,18) but not consistently in men.…”
Section: Discussionsupporting
confidence: 85%
“…(19) This database is mandatory and exhaustive, as the funding of each hospital is calculated from this hospital coding. The accuracy and quality of the coding is checked every month in each hospital by a dedicated physician, and an external audit is performed on a yearly basis by physicians of the national medical insurance services.…”
Section: Methodsmentioning
confidence: 99%
“…The stable rates of hip fracture amongst women that we observed in the present study are consistent with many other studies of populations in the developed world, some of which have even documented a decline in age-and sex-adjusted rates [1]. Thus studies in USA [7], Canada [8], Austria [28], France [29], Australia [30] and New Zealand [31] have demonstrated declining age-and sex-specific rates of hip fracture over recent decades, often following an increase in rates in the decades prior. In the UK, a plateau in rates of age-adjusted hospital admission for hip fracture [32] was observed over the years 1989 to 1998.…”
Section: Discussionsupporting
confidence: 81%
“…It was higher than that recently reported in Eastern and Central European [19][20][21]28] and Western European countries [31,32,34,36,37]. The SIR in men was comparable to that in Finland, Hungary and the Czech Republic [10,15,33,38] but lower than in the group of countries with the highest incidence in Europe [10,13,14,17,29,30].…”
Section: Discussioncontrasting
confidence: 46%